2011 Annual International Conference of the IEEE Engineering in Medicine and Biology Society 2011
DOI: 10.1109/iembs.2011.6090142
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical characterization of neural electrodes based on PDMS-parylene C-PDMS sandwiched system

Abstract: Manufacturing of neural electrodes based on metal foil and silicone rubber using a laser is a simple and promising method. A handicap of such electrode arrays is the mechanical robustness of the thin metal tracks that connect the electrode sites with the interconnection pads. Embedding of structured parylene C foil in silicone rubber turned out to be an interesting method to increase the robustness. Test samples with 12.5 μm thick platinum tracks and a 15 μm thick embedded and RIE-structured parylene C foil sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
3
3
2

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 8 publications
0
12
0
Order By: Relevance
“…PDMS offers good insulation, vibration absorption, good adaptability to tissue's deformation due to excellent elasticity (Wu et al, 1999 ; Kim et al, 2011 ; Minev et al, 2015 ; Alt et al, 2016 ), diffusional resistance to contamination solutes (Wu et al, 1999 ), good optical transparency (Jeong et al, 2015 ), hardly observed degradation (Alt et al, 2016 ), lower foreign body response (Bae et al, 2014 ), as well as low cost and availability. The most notable quality of PDMS is its superior, FDA-approved biocompatibility (Henle et al, 2011a ; Bae et al, 2014 ) for chronic implants (USP class VI). It is one of the few packaging materials that have been tested for long-term implantation (Brindley et al, 1986 ; Schiavone et al, 2018 ).…”
Section: Packaging and Substrate Materialsmentioning
confidence: 99%
“…PDMS offers good insulation, vibration absorption, good adaptability to tissue's deformation due to excellent elasticity (Wu et al, 1999 ; Kim et al, 2011 ; Minev et al, 2015 ; Alt et al, 2016 ), diffusional resistance to contamination solutes (Wu et al, 1999 ), good optical transparency (Jeong et al, 2015 ), hardly observed degradation (Alt et al, 2016 ), lower foreign body response (Bae et al, 2014 ), as well as low cost and availability. The most notable quality of PDMS is its superior, FDA-approved biocompatibility (Henle et al, 2011a ; Bae et al, 2014 ) for chronic implants (USP class VI). It is one of the few packaging materials that have been tested for long-term implantation (Brindley et al, 1986 ; Schiavone et al, 2018 ).…”
Section: Packaging and Substrate Materialsmentioning
confidence: 99%
“…For this study a laser-based manufacturing process was developed in order to create tracks individually coated with parylene C. An additional polymer besides the silicon rubber should benefit both, the mechanical and the electrical properties of the array. In contrast to the intermediate parylene layer in [5], arrays with coated integrated tracks spare at least three silicone layers compared to our state-ofthe-art method. Thus the whole electrode array remains more flexible while the fragile metal tracks are individually protected.…”
Section: Introductionmentioning
confidence: 78%
“…3. For the meander design an opening angle θ of 60° was chosen in accordance with actual electrode designs [5]. Other dimensions for the specimens were: Straight coating width w3 = 1.1 mm, track width w1 = 150 µm, metal foil thickness d1 = 12.5 µm and coating thickness d2 = 10 µm.…”
Section: Mechanical Testsmentioning
confidence: 99%
See 1 more Smart Citation
“…Laser fabricated electrode arrays are thicker (several 100 µm) than thin-film electrode arrays (several 10 µm) and thus only the later come into consideration for intrafascicular electrode arrays. Reasons for the increased thickness lie within the general greater thickness of the used materials (metal foils: 25 µm, sputtered platinum: 300 nm) as well as the fact that nanosecond laser technology melts the boundaries of the metal foil, which then needs additional silicone rubber and supplementary layers to provide mechanical strength [4]. These problems can be addressed with new shortpulse laser technology that allows for smaller feature size, higher integration density and new base materials like Parylene C that already has approval of the US Food and Drug Administration [5].…”
Section: Introductionmentioning
confidence: 99%